A New Approach to Enhancing Radiation Hardness in Advanced Nuclear Radiation Detectors Subjected to Fast Neutrons - Aref Vakili; Mahsa Farasat; Antonino La Magna; Markus Italia; Lucio Pancheri (Instruments)
Low-Gain Avalanche Diodes (LGADs) are critical sensors for the ATLAS and CMS timing detectors at the High Luminosity Large Hadron Collider (HL-LHC), offering enhanced timing resolution with gain factors of 20 to 50. However, their radiation tolerance is hindered by the Acceptor Removal Phenomenon (ARP), which deactivates boron in the gain layer, reducing gain below the threshold for accurate timing. This study investigates the radiation hardness of thin, carbon-doped LGAD sensors developed by Brookhaven National Laboratory (BNL) to address ARP-induced limitations. Active dopant profiles in the gain layer, junction, and bulk were measured using a Spreading Resistance Probe (SRP) profilometer, and the effects of annealing and neutron irradiation at fluences of 3 × 1014, 1 × 1015, and 3 × 1015 neq/cm2 (1 MeV equivalent) were analyzed. Low carbon dose rates showed minimal improvement due to enhanced deactivation, while higher doses improved radiation hardness, demonstrating a non-linear dose–response relationship. These findings highlight the potential of optimizing gain layers with high carbon doses and low-diffusion boron to extend LGAD lifetimes in high-radiation environments. Future research will refine carbon implantation strategies and explore alternative approaches to further enhance the radiation hardness of LGADs.